PENGEMBANGAN APLIKASI WEB KOST-KOSTAN DI KOTA BATAM DENGAN METODE EXTREME PROGRAMMING - Daniel Apdianto Herman; Michael Michael (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
On yearly basis, many new students coming from outside the city who plan to continue their education in a new environment or place. Because of this, the need for housing also increases proportionally, especially in the areas that are close to university institutions. But often due to the limited information confused the prospective and new coming students in finding the housing to live on. Therefore, the author intends to develop a boarding house web application that can provide this information and connect the boarding house provider with the boarding house seeker. This is also very flexible as it can be accessed anytime and anywhere as long as it has an internet connection. The author applies the Extreme Programming (XP) methodology during this research process. At the end of the research, a boarding house web application will be produced where the boarding house owner can promote their housing and the boarding house seeker can find the desired housing with all the information listed inside the application. From this research, the author concludes that the boarding house application is needed at this time. And the application of XP methodology is very suitable because of the short period of research and of course because the XP methodology is very structured.